The Future of Revolution - Breyer, Megan (New Agenda: SA Journal of Social and Economic Policy, 2025)
Jasper Bernes’s The Future of Revolution is not an easy book to pick up for a reader less familiar with the history of communist thought. It can feel dense, but it reengages communist ideas with a sense of possibility. Rather than offering a new idea, Bernes re-examines old and sometimes forgotten revolutionary texts to ask how they might illuminate the future. His contribution thus echoes Marx’s remark that “revolutions dress themselves up in the costumes of the past in order to speak the poetry of the future”.